Respuesta :

we are given

[tex]\frac{6^a6^a}{36^b} =36^x[/tex]

now, we can use property of exponent

[tex]m^p *m^p=(m)^{2p}[/tex]

so, we can write as

[tex]6^a *6^a=(6)^{a+a}[/tex]

[tex]6^a *6^a=6^{2a}[/tex]

[tex]6^a *6^a=(6^{2})^a[/tex]

[tex]6^a *6^a=(36)^a[/tex]

now, we can plug back

[tex]\frac{36^a}{36^b} =36^x[/tex]

we can use property of exponent as

[tex]\frac{w^m}{w^n} =w^{m-n}[/tex]

we can write as

[tex]36^{a-b} =36^x[/tex]

now, we can compare both sides exponents

and we will get

[tex]x =a-b[/tex]................Answer